A cryptic clue - Gilbert, Victoria (Gilbert, Victoria. Hunter and Clewe mystery, 2023)
A retired librarian is hired by an eccentric collector who needs an archivist for his huge, expanding compendium of rare books, where she discovers the dead body of her new employer's ex-girlfriend, who was also the heir to a pharmaceutical fortune.